Transforming policy into action : facilitating teacher change in a Jamaican innovation. - EVANS, Hyacinth (1997)
Reports the results of research on the Reform of Secondary Education programme in three types of secondary school in Jamaica. Examines the cases of two of those schools - one where the innovation was successfully implemented, and the other where it was not - in order to discover the features of the initiation which are associated with teachers' motivation to adopt the new teaching methods, and the administrative features of the schools which facilitated successful implementation.